The influence of a transverse shift of torsatron magnetic surfaces on their parameters - Kotenko, V. G. (Вопросы атомной науки и техники, 2005)
The paper deals with the influence of the transverse shift (or axial shift along the axis of torus rotation) of magnetic surfaces on their parameters in a calculation model of the l=2 torsatron magnetic system. The shift can be realized by means of a special-purpose controlling coil of a helical type. The coil action combined with the well-known action of common annular controlling coil is considered as an instrument for two-dimensional control of the plasma core position in stellarator-type plasma devices. В роботі з’ясовано вплив поперечного зміщення (або ж осьового зміщення вздовж осі обертання тора) магнітних поверхонь на їх параметри в моделі l=2 торсатрона. Зміщення здійснюється за допомогою спеціальної коректуючої обмотки гвинтового типу. Дія цієї обмотки в поєднанні з дією звичайної кільцеподібної коректуючої обмотки надає можливість 2-вимірного контролю за положенням плазмового шнура в плазмових пастках стелараторного типу. В работе выяснено влияние поперечного смещения (или осевого смещения вдоль оси вращения тора) магнитных поверхностей на их параметры в расчетной модели l=2 торсатрона. Смещение осуществляется с помощью специальной корректирующей обмотки винтового типа. Действие этой обмотки в сочетании с обычной кольцеобразной корректирующей обмоткой позволяет осуществить 2-мерный контроль положения плазменного шнура в плазменных ловушках стеллараторного типа.